Physical Problems and Social Stigma Faced by Leprosy Patients in a Hospital of Lalitpur - Mahat, Rasmita; Gurung, Bishnu (Janapriya Journal of Interdisciplinary Studies, 2024)
Leprosy is one of the critical health problem in the developing countries which affects physical, social and psychological aspects of human being. The study aimed to identify the physical problems and social stigma faced by leprosy patients in a hospital of Lalitpur focusing on prevalent myths and physical deformities caused by the disease. A descriptive cross-sectional research design and non-probability purposive sampling technique was used to conduct this study through interviewer administered questionnaire among 109 leprosy patients at Anandaban hospital and Patan’s Clinic. The study assessed public attitudes toward leprosy patients using the Explanatory model interview catalogue stigma scale (EMIC) and identified disfigurement and ulcer by direct observation and disability using the WHO disability grading tool. Data analysis was done using SPSS version 16. Inferential statistics Mann Whitney U and (chi-square tests) was used at 5% level of significance. The findings revealed that a significant portion of respondents were aged 40-59 years. Most respondents reported physical problems, predominantly grade 1 disability. Many patients disclosed their condition to relatives, over half kept it secret, and a substantial majority experienced shame or embarrassment. Nearly half of the respondents perceived higher stigma. There was a significant associations of physical problems with age, occupation, and disease duration. The study emphasizes the importance of raising awareness at all community levels and the knowledge regarding medical advances of the leprosy to mitigate disease concealment, low self-esteem and shame or embarrassment and address the associated social stigma.